Penanaman Nilai-nilai Multikultural Melalui Pendidikan Agama di SMA Bopkri 2 Yogyakarta - Artikasari, Yuli (Jurnal Pendidikan Kristen dan Ilmu Teologi Marturia, 2020)
AbstractThe research aims to describe the cultivation of multicultural values in SMA BOPKRI 2 Yogyakarta through religious education. The method used is qualitative naturalistic with data collection techniques in the form of in-depth interviews with the subjects of the Human Resources Bopkri 2 High School in Yogyakarta and analyzed several related documents. The research data were analyzed using Miles and Huberman's analytical theory with the steps of data collection, data reduction, data presentation, and conclusion drawing. The study then found that the inculcation of multicultural values was by the vision and mission of the school which was based on indicators of religious diversity, intellectual diversity, differences in cultural ethnicity, social conditions, differences in talent interests, and physical conditions (disability). The multicultural values contained in the planting of multicultural values in SMA BOPKRI 2 Yogyakarta are the values of diversity, the importance of equality, values of tolerance, values of empathy, values of friendship, and values of patriotism. AbstrakPenelitian bertujuan mendeskripsikan penanaman nilai-nilai multikultural di SMA BOPKRI 2 Yogyakarta melalui pendidikan agama. Metode yang digunakan adalah kualitatif naturalistik dengan teknik pengumpulan data berupa wawancara mendalam kepada subyek bidang Sumber Daya Manusia SMA BOPKRI 2 Yogyakarta dan menganalisis beberapa dokumen terkait. Data-data penelitian dianalisis menggunakan teori analisis Miles dan Huberman dengan langkah kerja pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian ini kemudian menemukan bahwa penanaman nilai-nilai multikultural telah bersesuaian dengan visi misi sekolah yang didasarkan pada indikator keragaman agama, keberbedaaan intelektual, keberbedaan suku budaya, kondisi sosial, perbedaan minat bakat, dan kondisi fisik (disabilitas). Adapun nilai-nilai multikultural yang terkandung dalam penanaman nilai-nilai multikultural di SMA BOPKRI 2 Yogyakarta ialah nilai keberagaman, nilai kesetaraan, nilai toleransi, nilai empati, nilai persahabatan, dan nilai cinta tanah air.